Low surface electromagnetic waves at the metasurface ⁄ dissipative dielectric interface - Galaydych, V.K.; Sporov, A.E.; Olefir, V.P.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2020)
The possibilities of the slow surface electromagnetic waves propagation along the flat boundary of a metasurface with a dissipative dielectric are studied. The metasurface is a thin flat slab of metamaterial with simultaneously negative permittivity and permeability with “amplification”. All media were assumed to be isotropic. Dispersion dependences are obtained for the eigenmodes of such a waveguide structure. The possibility of full compensation of the energy losses of surface waves by the appropriate choice of the “gains” values is demonstrated.